Nano-sized MX carbonitrides contribute to the stability of mechanical properties of martensite ferritic steel in the later stages of long-term aging. (15th August 2019) - Xu, Yuantao; Li, Wei; Wang, Mingjia; Zhang, Xiying; Wu, Yun; Min, Na; Liu, Wenqing; Jin, Xuejun
Abstract: The coupling effects between MX carbonitrides, M2 X phase, M23 C6 carbides, and the Laves phase and their influences on the mechanical properties during long-term aging at 650 °C were studied. Before aging for 40500 h, the subgrain size is mainly stabilized by M23 C6 carbides, whose pinning effect gradually weakens with the coarsening during long-term aging. However, after aging for 40500 h, the volume fraction of nano-sized MX carbonitrides gradually increases and compensates for the loss of pinning effect from M23 C6 carbides, working together with the M23 C6 carbides to hinder the coarsening of the subgrain. The increase in the volume fraction of nano-sized MX carbonitrides from 40500 h to 49500 h, mainly resulting from the gradual dissolution of M2 (C, N) carbonitrides, which not only contributes to the stability of the strength through the pinning effect and precipitation strengthening, but also benefits the ductility by suppressing the rapid coarsening of the Laves phase through the strong competition for Si between the Laves phase and MX. An unusual combination of stable strength and stable ductility in the later stages of long-term aging at 650 °C (approximately 9000 h) was achieved. Graphical abstract: Image 1